HUMOR ABOUT THE LIVES OF ASIAN IMMIGRANTS IN THE US IN RONNY CHIENG: ASIAN COMEDIAN DESTROYS AMERICA! - Nurhantoro, Tri Septa; Kristiawan, Yohanes Angie; Sriyanto, Yanus Purwansyah; Novanda, Mira; Petria, Margaretha Resa (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
This article explores humor about the lives of Asian immigrants in the United States as depicted in Ronny Chieng: Asian Comedian Destroys America! (2019). The article is conceived through qualitative discourse analysis approach to examine how Chieng utilizes comedic techniques to highlight the challenges and contradictions of Asian immigrant experiences in the US through thematic analysis, the study identifies key themes in Chieng’s performance: cultural differences on American consumerism, admiration and dissatisfaction, racial marginalization, and family expectations. The analysis applies Berger’s humor theories to understand the construction of humor criticizing American society. By employing exaggeration, irony, language play, high-energy delivery, and reversal, Chieng not only entertains but also provides a platform for the audience to engage with their lives through comedy. The study concludes that humor serves as a powerful tool for discussing Asian immigrant experiences, breaking stereotypes, and fostering empathy. Chieng’s stand-up comedy show demonstrates how narrative comedy can be an effective means of social criticism, bridging cultural divides while making complex issues more accessible to broad audiences.